Design and Query Strategies to Hypermedia Applications - Gordillo, Silvia Ethel (1998)
In this paper we propose an object-oriented model for designing hypermedia applications. As the object-oriented paradigm allows complex and user-defined types, nonconventional and nonatomic attributes, we can take advantage of these capabilities, not only for information modelling, but also for providing alternative ways for accessing information. A query language is then presented; it is based on an Object-Oriented Database System query language. It combines features of object-oriented databases queries and primitives for hypermedia navigation. The language offers the possibility of querying both the application-domain information, and allowing the designers to obtain information about the schema of the application. We present some examples of the use of the object-oriented model and the query language.